Complete Genome Sequence of the Halophilic Methylotrophic Methanogen Archaeon Methanohalophilus portucalensis Strain FDF-1(T) - L’Haridon, Stéphane (Genome Announc, 2018)
We report here the complete genome sequence (2.08 Mb) of Methanohalophilus portucalensis strain FDF-1(T), a halophilic methylotrophic methanogen isolated from the sediment of a saltern in Figeria da Foz, Portugal. The average nucleotide identity and DNA-DNA hybridization analyses show that Methanohalophilus mahii, M. halophilus, and M. portucalensis are three different species within the Methanosarcinaceae family.